Description of a new species of the genus Woznessenskia from Xizang, China (Orthoptera: Gryllacrididae) - Zhang, Zi-Heng; Tian, Hao-Hu; Long, Xiao-Yu; Yin, Zi-Xu; Li, Kai; He, Zhu-Qing (Zootaxa, 2024)
The gryllacridid genus Woznessenskia Gorochov, 2002 comprises 13 extant species from Asia, with 8 species reported from China and 5 species reported from Vietnam. A new species from Xizang, China, Woznessenskia lianhua sp. nov., is reported in this paper.